Is more capability always beneficial for firm performance? Market orientation, core business process capabilities and business environment. Issue 13 (1st September 2016) - Jaakkola, Matti; Frösén, Johanna; Tikkanen, Henrikki; Aspara, Jaakko; Vassinen, Antti; Parvinen, Petri
ABSTRACT: This study examines the role of capabilities in core marketing-related business processes–product development management (PDM), supply chain management (SCM) and customer relationship management (CRM)–in translating a firm's market orientation (MO) into firm performance. The study is the first to examine the interplay of all three business process capabilities simultaneously, while investigating how environmental conditions moderate their performance effects. A moderated mediation analysis of 468 product-focused firms finds that PDM and CRM process capabilities play important mediating roles, whereas SCM process capability does not mediate the relationship between MO and performance. However, the relative importance of the capabilities as mediators varies along the degree of environmental turbulence, and under certain conditions, an increase in the level of business process capability may even turn detrimental.